The Effect of Picture Series on Students’ Reading Comprehension of Analytical Exposition - muhammad kristiawan; Yuli novita (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
This research was aimed at examining the effect of picture series on students’ reading comprehension. Thus, the experiment (XI IPA3) and control groups (XI IPA 2) were created: the experiment group was taught by Picture Series while the control group was PowerPoint. The total sample of this research are 60 students of science High School 1 Ulakan Tapakis, West Sumatera,who were enrolled in two classes of grade XI IPA 3 and grade XI IPA 2 in 2015/2016 academic years. This research was experimental design, the instruments were observation sheet and reading test. The result showed that from mean score of experimental class 87.87 and mean score of control class 84.67. The data were analyzed by using SPSS program for windows version 18. The result of readings score showed that 2,42 >1,68 or sig 0,003 < 0,05. It showed that teaching reading by using Picture Series was accepted statistically. It can be concluded that Picture Series gave significant effect on students’ reading comprehension at grade XI High School 1 Ulakan Tapakis Keywords: Picture Series, Reading comprehension, Analytical Exposition Text